2017
DOI: 10.1007/s00737-017-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of midwifery carer moderates the effects of prenatal maternal stress on postnatal maternal wellbeing: the Queensland flood study

Abstract: Poor postnatal mental health is a major public health issue, and risk factors include experiencing adverse life events during pregnancy. We assessed whether midwifery group practice, compared to standard hospital care, would protect women from the negative impact of a sudden-onset flood on postnatal depression and anxiety. Women either received midwifery group practice care in pregnancy, in which they were allocated a primary midwife who provided continuity of care, or they received standard hospital care prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
0
40
0
4
Order By: Relevance
“…In the included studies, 12 were randomized controlled trials (32,51-61), whereas five were controlled clinical trials (35,(62)(63)(64)(65). Significant reduction (P<0.05) in depression and anxiety was reported in 13 of the included studies which received midwife-supported psychotherapy (19,32,51,52,(54)(55)(56)(57)(58)(60)(61)(62)64). Two studies reported an insignificant reduction (P>0.05) (53,59), and two studies reported no effect (63,65), of midwife-supported psychotherapy on depression, anxiety and maternal health-status outcome during the antenatal stage of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the included studies, 12 were randomized controlled trials (32,51-61), whereas five were controlled clinical trials (35,(62)(63)(64)(65). Significant reduction (P<0.05) in depression and anxiety was reported in 13 of the included studies which received midwife-supported psychotherapy (19,32,51,52,(54)(55)(56)(57)(58)(60)(61)(62)64). Two studies reported an insignificant reduction (P>0.05) (53,59), and two studies reported no effect (63,65), of midwife-supported psychotherapy on depression, anxiety and maternal health-status outcome during the antenatal stage of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…The average baseline, follow-up assessments for the included studies was performed at 19.8±2.3 and 35.7±2.3 weeks, respectively. However, from the included studies six did not report the initial baseline stage of assessment (19,54,55,60,63,64), whereas eleven did not report the stage at which the follow-up assessment was perfor med (19,32,51,(55)(56)(57)(58)60,(63)(64)(65).…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Research on prenatal exposure to the pandemic may consider how prenatal stress and maternal immune activation are affected by, among others; (1) the risks of maternal coronavirus infection, (2) the effect of social distancing on stress and its interaction with partner support (Brock et al, 2014), (3) the effect of social distancing on access to perinatal care (Kildea et al, 2018), and (4) the effects of urbanicity, notably in a context of potential decrease in air pollution and traffic noise (Cai et al, 2017).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Evidence suggests that the negative effects of adversity in prenatal life can be mitigated if antenatal care is sustained. 12 During the Queensland floods of 2011, continuity of care to pregnant women not only protected them against adverse pregnancy outcomes, but also had positive effects on children's future neurodevelopment. 13 Whilst the pandemic persists, this is a critically important message to maternity care providers in all global settings.…”
mentioning
confidence: 99%